PERAN PERATURAN MENTRI KOMUNIKASI DAN DIGITAL NOMOR 9 TAHUN 2026 DALAM MITIGASI ANCAMAN NIRMILITER DAN PENGUATAN KETAHANAN NASIONAL GENERASI MUDA - Sigit Tri Atmaja Priya Hutama; Bukhari Muslim; Esti Perwitasari; Rr. Nanik Setyowati; Siti Maizul Habibah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The exponential digital transformation has catalyzed complex non-military threats, including illegal online gambling, disinformation, and cybercrime, which jeopardize social stability and national resilience, particularly among Indonesia’s youth. Despite the urgency of digital regulation as a mitigation tool, academic analysis regarding the role of Minister of Communication and Digital Regulation Number 9 of 2026 remains limited. This study aims to comprehensively analyze the substance, mechanisms, and implications of this regulation as an instrument for mitigating non-military threats and strengthening youth national resilience by integrating legal, defense, and digital governance perspectives. The research employs a qualitative descriptive approach using systematic library research. Data were gathered from primary and secondary sources published between 2021 and 2025, subsequently analyzed through qualitative content analysis and source triangulation. The findings indicate that effective digital regulation must be built upon three integrated pillars: an adaptive legal framework, comprehensive technical data governance standards, and responsive multi-stakeholder institutional mechanisms. Regulation No. 9 of 2026 demonstrates high strategic relevance through access restrictions on online gambling, user identity verification, and cross-agency law enforcement coordination. Furthermore, the integration of data protection and digital literacy contributes significantly to the national resilience of the younger generation. Theoretically, this research offers an integrative analytical framework connecting regulatory compliance theory with risk-based information governance. Practically, it provides evidence-based policy recommendations for stakeholders to design effective digital regulations that protect the youth and fortify Indonesia’s national resilience in the digital era. ABSTRAK Transformasi digital eksponensial memicu ancaman nirmiliter seperti judi online, disinformasi, dan kejahatan siber yang mengancam stabilitas sosial serta ketahanan nasional, khususnya bagi generasi muda. Meskipun krusial, kajian mengenai peran Peraturan Menteri Komunikasi dan Digital Nomor 9 Tahun 2026 dalam memperkuat ketahanan nasional masih sangat terbatas. Penelitian ini bertujuan menganalisis secara komprehensif substansi, mekanisme, dan implikasi regulasi tersebut sebagai instrumen mitigasi ancaman nirmiliter melalui integrasi perspektif hukum, pertahanan, dan tata kelola digital. Metodologi yang digunakan adalah deskriptif kualitatif dengan metode studi pustaka sistematis (systematic library research). Data dikumpulkan dari sumber primer dan sekunder periode 2021–2025, kemudian dianalisis menggunakan teknik analisis isi kualitatif dan triangulasi sumber. Hasil penelitian menunjukkan bahwa regulasi digital yang efektif harus dibangun di atas tiga pilar: kerangka hukum adaptif, standar teknis tata kelola data, dan mekanisme multi-stakeholder. Permen Komdigi No. 9 Tahun 2026 terbukti memiliki relevansi strategis tinggi melalui pembatasan akses judi online, verifikasi identitas, dan koordinasi penegakan hukum lintas instansi. Selain itu, integrasi perlindungan data serta literasi digital ditemukan berkontribusi signifikan terhadap penguatan ketahanan nasional generasi muda. Secara teoretis, penelitian ini menawarkan kerangka analisis integratif yang menghubungkan teori kepatuhan regulasi dengan tata kelola informasi berbasis risiko. Secara praktis, studi ini memberikan rekomendasi kebijakan berbasis bukti bagi pemangku kepentingan untuk melindungi generasi muda dan memperkokoh ketahanan nasional Indonesia di era digital.